APPLYING INTELLECTUAL CAPITAL IN IMPROVING AGRI-INDUSTRY AT REPUBLIC OF SERBIA - Radenković, Sonja D.; Šaranović, Jelena; Stojanović, Boban; Kostić, Zorana; Jokić, Bojan (Economics of Agriculture, 2018)
Analysis of the economic framework for doing business between Serbia and Autonomous Province of Kosovo and Metohija, that is under the interim civil and military administration of the United Nations, according to UN Resolution 1244 (hereinafter referred to as Kosovo*) aims to point of the need to eliminate barriers in doing business between Serbia and Kosovo*, making recommendation for improving the business environment. The research involved experts analyzed legal regulations governing the business environment in Kosovo* and carried out the research. They interviewed business people and representatives of companies from central Serbia and Kosovo*. The results of the survey enable the creation of a wider picture of company operations when crossing of the administrative crossings, identifying disturbances in the passage of goods and services, as well as formulating proposals to overcome existing barriers in doing business between business entities in central Serbia and the Autonomous Province of Kosovo and Metohija.